KAJIAN FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PRODUKTIVITAS PETANI ASPARAGUS DI KECAMATAN PETANG KABUPATEN BADUNG - Artanegara, I Made; Setiawina, I Nyoman Djinar; Djayastra, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
Inequalities and the issue of globalization has implications for the acceleration of economic development in a focused area through the development of the region and its flagship product. Program OVOP (One Village One Product) agriculture asparagus in District Petang Badung district is agricultural, excellent products which have marketing potential of local and international (export), as well as value-added products, in order to compete with products from outside, increasing the income of rural people, reduce urbanization.  This study aimed to analyze the influence; 1) training, education, age, land area, number of employees, work experience, and capital to total production of asparagus. 2) training, education, age, land area, number of employees, work experience, capital and production quantities of the productivity of farmers asparagus. 3) indirect training, education, age, land area, number of employees, work experience, and capital to productivity through production quantities of asparagus farmers in the district of Badung regency Petang. The data sources used, there are two primary data obtained from interviews to farmers asparagus and secondary data obtained from cooperative partnership in the District OVOP Petang, Badung regency. Data collection methods used were interviews and questionnaires, with a number of respondents as many as 110 people. The analytical tool used is descriptive analysis and path analysis.
Keywords: OVOP, productivity, the amount of productio